2004
DOI: 10.1063/1.1792391
|View full text |Cite
|
Sign up to set email alerts
|

Are microbubbles necessary for the breakdown of liquid water subjected to a submicrosecond pulse?

Abstract: Microbubble-based model analysis of liquid breakdown initiation by a submicrosecond pulse J. Appl. Phys. 97, 113304 (2005); 10.1063/1.1921338 Breakdown threshold and localized electron density in water induced by ultrashort laser pulses Electrical breakdown in homogeneous liquid water for an ϳ100 ns voltage pulse is analyzed. It is shown that electron-impact ionization is not likely to be important and could only be operative for low-density situations or possibly under optical excitation. Simulation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…We have also demonstrated through Monte Carlo calculations that freeelectron transport and possible electronic impact ionization in bulk water would be virtually absent. 21 The numerical analysis quantitatively demonstrated that strong elastic scattering coupled with the highly isotropic angular deflections work to prevent electrons from picking up the requisite ionization energy. As a result, neither electron-initiated charge creation within the homogeneous bulk nor the electronic injection process at the cathode can have much relevance for breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated through Monte Carlo calculations that freeelectron transport and possible electronic impact ionization in bulk water would be virtually absent. 21 The numerical analysis quantitatively demonstrated that strong elastic scattering coupled with the highly isotropic angular deflections work to prevent electrons from picking up the requisite ionization energy. As a result, neither electron-initiated charge creation within the homogeneous bulk nor the electronic injection process at the cathode can have much relevance for breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…35 In the case of sub-microsecond discharges, it has been proposed that streamer propagation is triggered by field emission at the interface of pre-existing microbubbles, in which electron impact ionization occurs. 36,37 In the case of microsecond or longer pulsed discharges, a bubble theory associated with thermal effects is most likely to be the main mechanism. A theoretical model has shown that Joule heating leads to the evaporation of liquid and the formation of gas bubbles, in which an electrical discharge propagates.…”
mentioning
confidence: 99%
“…The attachment loss term A is usually defined in the literature [9][10][11] through the attachment rate  a as:…”
Section: Numerical Modelmentioning
confidence: 99%
“…In order to perform a more detailed analysis of the field emission at the cathode in that experiment, the model described in the previous section is used. As in the literature [9][10][11], the negative ion mobility  n is taken as the average electrohydrodynamic (EHD) mobility (10 -7 m 2 V -1 s -1 [5]) while the attachment rate constant  a is taken from the measured zero-field lifetime of electronic charges (500 ns for cyclohexane [5]). As shown in Fig.…”
Section: A Field Emission At the Cathodementioning
confidence: 99%
See 1 more Smart Citation